Multimodalidade em questões do ENEM: interpretando gêneros discursivos por meio da análise das linguagens verbal e não verbal - Ribeiro, Débora Maria Rodrigues (2025)
This research aims to investigate how verbal and nonverbal languages are used to construct the meanings of motivating texts in Enem questions that require reading skills that reach verbal and nonverbal resources. To this end, this study analyzes questions from Enem exams in the area of Languages and Codes and their Technologies in light of the theories of Multimodality and Multiliteracies to verify the occurrence of multimodal texts, how these texts are organized to produce meanings and the reading skills that are required to understand these texts. To achieve our objective, we followed the theoretical guidelines of Kress and van Leeuwen (2006); Vieira (2010) and Vieira and Silvestre (2015) to recognize and identify the presence of multimodal texts in Enem questions; the theoretical-methodological steps of Kress and van Leeuwen (2006) to analyze how multimodal texts are used to compose the meanings in the questions, in addition to following the precepts of Cope and Kalantzis (2000) and Rojo and Moura (2012) to analyze how multiliteracies are required from the reader to solve the question. We used as corpus questions from the Enem exams of the years 2019, 2020 and 2021 that explore verbal and non-verbal language. In our analysis, we used the categories proposed by the Visual Design Grammar of Kress and van Leeuwen (2006) for multimodal texts, which consist of the representational, interactional and compositional metafunctions, and as a category of analysis of multiliteracies we used the skills of the multiliterate reader, namely, functional user reader, meaning-creating reader, critical analytical reader and transformative reader. The results obtained show us that textual meanings are constructed by the association of verbal and nonverbal languages, which, together, complement each other to give meaning to the texts that make up the questions on the Enem exam. We found that reading and understanding these texts requires much more than the verbal literacy that our students acquire in elementary school. Through the categories used in the analyses, it was possible to perceive several meanings that many do not perceive in a superficial reading. Motivational texts require the reader to have multiliterate experience, as it is necessary to use a series of knowledge within the scope of various textual genres, their experience as a reader with linguistic and extralinguistic knowledge, in addition to using their world knowledge to be successful in solving them. We conclude that the Enem exams have required students to have reading skills that go beyond the understanding of the verbal text, thus reinforcing the need for students to be literate not only verbally, but also visually.